1996
DOI: 10.1111/j.1476-5381.1996.tb15595.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β stimulation of 45 Ca2+ release from rat striatal slices

Abstract: 1 Previous observations that centrally injected interleukin-lB (IL-iI) into rabbits induces a sustained rise in cerebrospinal fluid (CSF) Ca2+ concentration ([Ca2+]) as well as fever, prompted us to undertake an in vitro study to corroborate the in vivo results and gain insight as to the source and mechanism of IL-1/I-induced Ca2+ mobilization. 2 IL-1I treatment of rat striatal slices preloaded with 45Ca2 + elicited a rise in spontaneous 45Ca2+ release which was dose-dependent, delayed in onset and of extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Additional in vitro studies showed increased Ca 2ϩ efflux from rat striatum treated with IL-1␤ and antagonism of this effect by a specific IL-1 receptor antagonist protein. This explained the mechanism responsible for the increased Ca 2ϩ observed in CSF in vivo and also provided evidence that a specific receptor mediates Ca 2ϩ response (Palmi et al, 1996).The lag phase of the Ca 2ϩ response to IL-1␤ and the kinetic pattern of Ca 2ϩ release in these experiments were reminiscent of those of nitric oxide (NO) production by IL-1␤ in neurons (Bredt et al, 1991) and other cells (Inoue et al, 1993), suggesting that NO could be the intermediate messenger responsible for this effect. Additional support for this hypothesis is provided by reports showing that NO is involved in functions and molecular mechanisms controlling Ca 2ϩ homeostasis in many different cell systems (for review, see Clementi, 1998) and by the observation of increased synthesis-release of nitrite and nitrate, the breakdown products of NO in patients with fever (Leaf et al, 1990) or septic shock (Ochoa et al, 1991).…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Additional in vitro studies showed increased Ca 2ϩ efflux from rat striatum treated with IL-1␤ and antagonism of this effect by a specific IL-1 receptor antagonist protein. This explained the mechanism responsible for the increased Ca 2ϩ observed in CSF in vivo and also provided evidence that a specific receptor mediates Ca 2ϩ response (Palmi et al, 1996).The lag phase of the Ca 2ϩ response to IL-1␤ and the kinetic pattern of Ca 2ϩ release in these experiments were reminiscent of those of nitric oxide (NO) production by IL-1␤ in neurons (Bredt et al, 1991) and other cells (Inoue et al, 1993), suggesting that NO could be the intermediate messenger responsible for this effect. Additional support for this hypothesis is provided by reports showing that NO is involved in functions and molecular mechanisms controlling Ca 2ϩ homeostasis in many different cell systems (for review, see Clementi, 1998) and by the observation of increased synthesis-release of nitrite and nitrate, the breakdown products of NO in patients with fever (Leaf et al, 1990) or septic shock (Ochoa et al, 1991).…”
mentioning
confidence: 68%
“…Tissue preparation followed the method described previously (Palmi et al, 1996). Briefly, male albino Sprague Dawley rats weighing 300 Ϯ 50 gm were killed by decapitation and rapidly decerebrated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue preparation was according to a previously described protocol with slight modifications (Palmi et al ., 1996). Briefly, male albino Sprague‐Dawley rats weighing 300 ± 50 g were housed under standard conditions with food pellets and water ad libitum .…”
Section: Methodsmentioning
confidence: 99%
“…Our initial observations establishing a role of Ca 2+ in the mechanism of interleukin‐1β‐induced fever in mammals (Palmi et al ., 1992; Palmi et al ., 1994; Palmi et al ., 1996) led to the demonstration that interleukin‐1β‐associated NO production or NO released by some NO donors such as spermine‐ and diethylamine‐NONOates were responsible for intracellular Ca 2+ mobilization in human astrocytoma cells and in rat brain striatal slices perfused under normoxic conditions. In both these cases, the Ca 2+ responses were reversed concentration‐dependently by the NOS inhibitor N‐ω‐nitro‐L‐arginine methyl ester (L‐NAME) and by a combination of ruthenium red (RR) and heparin identifying ryanodine (RY)‐ and inositol‐(1,4,5)‐trisphosphate (IP 3 )‐sensitive Ca 2+ pools as sources of the Ca 2+ released (Meini et al ., 2000; Palmi & Meini, 2002).…”
Section: Introductionmentioning
confidence: 99%